Maternal antibiotic treatment during pregnancy attenuates the transport and absorption of maternal antibody IgG through TLR4 and TLR2 receptor - Ding, Yanan; Yao, Xiaofeng; Zhang, Haihan; He, Xi; Song, Zehe (Frontiers in Microbiology, 2023)
Maternal antibody IgG, the main antibody in colostrum, plays an important role in neonates protection. Commensal microbiota is closely related to host antibody repertoire. However, there are few reports on how maternal gut microbiota affects maternal antibody IgG transfer. In the present study, we investigated the effects of altering the gut microbiota (treated with antibiotics during pregnancy) on maternal IgG transportation and offspring absorption and explored its underlying mechanisms. Results showed that antibiotic treatment during pregnancy significantly decreased maternal cecal microbial richness (Chao1 and Obesrved species) and diversity (Shannon and Simpson). Plasma metabolome enriched significant changes in the process of bile acid secretion pathway, and the concentration of deoxycholic acid, a secondary metabolite of microorganisms was lowered. Flow cytometry analysis indicated that antibiotic treatment promoted the number of B cells and abated the number of T, DC and M1 cells in intestinal lamina propria of dams. Surprisingly, the serum IgG level in antibiotic treated dams was significantly increased, while IgG contents in colostrum was decreased. Moreover, pregnancy antibiotic treatment in dams was reduced the expression of FcRn, TLR4 and TLR2 in breast of dams and in duodenum and jejunum of neonates. Furthermore, TLR4−/− and TLR2−/− knock-out mice showed a lower FcRn expression in breast of dams and in duodenum and jejunum of neonates. These findings suggest that maternal intestine bacteria may affect the maternal IgG transfer through regulating the breast TLR4 and TLR2 of dams.